How elite-level soccer dynamics has evolved over the last three decades? Input from generalizability theory - Barreira, Daniel; Garganta, Júlio; Castellano, Julen; Machado, João; Anguera, M.Teresa (Cuadernos de Psicología del Deporte, 2015)
Soccer dynamics have evolved in response to environmental factors such as match status, type of competition, and competition stage. Observational analysis has shed light into the behavior of players, but few researchers have looked at the complexity of the interactions between players and their teams over time. Here we investigated the variables influencing the patterns of play and the evolution of tactical and technical behaviors through the last three decades. A retrospective inferential study was applied. SoccerEye observational instrument and recording software were used toobserve and record 45 matches and 6791 attacks from European and World Cup semi-finals and finals between 1982 and 2010. Publicly available broadcast footage was used for the analysis. Generalizability theory was used as the basis of the statistical analysis. The patterns of play changed by 31.4% from 1982 to 2010. Team dynamics were in;uenced by match status (28.0%), competition stage (26.5%), and game period (18.1%). During the last decade (2002–2010), teams tended to use less the dribble and running with the ball but to increase long passing rate. During 2002-2010 decade, the frequency of attacks down the wings was higher than in 1982–2000, probably a result of the numerical disadvantage of the attacking team in the area of play. Soccer dynamics have changed towards more teamwork and less individual work over the last 30 years. However, not only time, but also match status, competition stage, and game period have in;uenced the patterns of play.